The Influence Of Organizational Communication And Organizational Commitment On Employee Performance With Job Satisfaction As A Mediation Variable (Study On Employees Of Kinik Network Pt. Bhaksena) - SARI, Ida Ayu Wika Permata; DHARMANEGARA, Ida Bagus Agung; MARTADIANI, A.A. Media (International Journal of Environmental, Sustainability, and Social Science, 2024)
This research aims to determine the influence of organizational communication and organizational commitment on job satisfaction and organizational performance, either directly or through the role of mediating variables therein. The nature of this research is explanatory research, which aims to explain the causal relationship between the variables observed in this research. In this research, the author took the total population, namely 65 employees. Data was collected using a questionnaire and analyzed using the PLS program. Organizational communication has a positive and significant effect on employee performance. Organizational commitment has a positive and significant effect on employee performance. Organizational communication has a positive and significant influence on job satisfaction. Organizational commitment has a positive and significant effect on job satisfaction. Job satisfaction has a positive and significant effect on employee performance. Job satisfaction is a partial mediating variable in the relationship between organizational communication and employee performance. In a case study at PT. Bhaksena organizational communication directly has an influence on employee performance through job satisfaction as a mediating variable. Job satisfaction is a partial mediating variable in the relationship between organizational commitment and employee performance. In a case study at PT. Bhaksena organizational commitment directly has an influence on employee performance through job satisfaction as a mediating variable.